Effectiveness of Combined Ultrasound, Stretching and Strengthening Therapy Plantar Fasciitis Rehabilitation: A Case Study - Cicilia Febriani Hayuningrum; Sarah Tiurmida Monica; Yulsefni; Nur Khotimah Elfiyani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Plantar fasciitis is a common musculoskeletal condition and a leading cause of chronic heel pain, often disrupting daily functional activities. This study aimed to evaluate the effectiveness of combined ultrasound therapy, stretching, and strengthening in reducing pain, improving range of motion, muscle strength, and gait function in a patient with left-sided plantar fasciitis. A case study was conducted on a 55-year-old female diagnosed with left plantar fasciitis based on clinical assessment and MRI. The physiotherapy intervention was performed over six sessions within four weeks and consisted of ultrasound application (1 MHz, 1 W/cm², 10 minutes), gastrocnemius-soleus stretching, and strengthening exercises for intrinsic and extrinsic foot muscles (towel curl and theraband squat). Evaluations included pain intensity (VAS), range of motion (goniometer), muscle strength (MMT) and functional ability (FADI questionnaire). After six sessions, pain decreased from VAS 6 to 3, range of motion and muscle strength improved (MMT 3 to 4) and FADI score increased from 59% to 65%. These findings demonstrate that the combined therapy provided meaningful clinical improvements in a short period. The combination of ultrasound, stretching, and strengthening is effective in reducing pain and improving foot function in plantar fasciitis. This study supports multimodal physiotherapy as an efficient and clinically applicable rehabilitation strategy.